Mesoamerican reef system: damage for climate change and fillings - Gallegos Rojano, Iliana Zamira (2021)
The impacts to marine ecosystems are varied and not very visible, in this research we show the damage to a part of the Mesoamerican reef system due to different factors, including climate change and strandings. Through the analysis of the Protected Natural Areas of Mexico that are part of the system, it is clear that during 10 years 8,798.55 m2 of reefs have been lost, although the impacts are decreasing in recent years, we are still not sure that this is controlled.